Human health risk assessment from consumption of freshwater fish and crayfish containing mercury - Mariya A. Gustaytis; Irina N. Myagkaya (Bulletin of the Tomsk Polytechnic University Geo Assets Engineering, 2026)
Relevance. Mercury is one of the dangerous toxicants. And the food products are the main source of intake for the human body. Bioindication of mercury content in living organisms consumed by people allows identifying both the degree of their mercury contamination and the possible risks to the preservation of bioresources, and provides insights into the presence or absence of human health risks. Aim. To assess the safety of freshwater animals (fish, crayfish) consumed by residents of the territory affected by mining activities at the Novo-Ursk polymetallic deposit, and to identify possible human health risks. Methods. The total Hg content was determined by the AAS method (analyzer "RA-915M" with the pyrolytic attachment "RP-91S", Lumex, Russia) according to the method M 03-09-2013. The geochemical indices: provisional tolerable daily intake, maximum permissible limit (CRlim), maximum permissible meals per month, target hazard quotient, were used to assess the risks of the fish and crayfish consumption impact on human health. Results. Mercury concentrations in the fish exceed the maximum permissible concentration only in predatory ones, sampled in 5 km from the mouth of the drainage stream into the Ur River. The Hg content in the crayfish, living in the flooded quarry of Ursk mine, is higher than the maximum permissible concentration. For these sampling sites and variety fauna, the provisional tolerable daily intake values close to its reference were also recorded, as well as a smaller number of safe consumption portions per month and excess of target hazard quotient (there is a risk of non-carcinogenic diseases). For the remaining sampling sites carried out in the ore conditions of the Novo-Ursk deposit, the small number of safe consumption portions per month recorded in accordance with the reference values maximum permissible concentration, provisional tolerable daily intake and target hazard quotient indicate the need to prohibit the consumption of fish because of its low safety. Thus, it is not recommended to eat fish caught from water bodies that are affected by the Novo-Ursk deposit. Mercury concentration in fish of only the area located above of dispersion halo of the Novo-Ursk deposit is standard for safe consumption. The maximum permissible concentration and target hazard quotient (long-term consumption) for fish and crayfish are more corresponding to the possibility of safe consumption of products, compared to the provisional tolerable daily intake. For citation: Gustaytis M.A., Myagkaya I.N. Human health risk assessment from consumption of freshwater fish and crayfish containing mercury. Bulletin of the Tomsk Polytechnic University. Geo Assets Engineering, 2026, vol. 337, no. 8, pp. 244–254. http://doi.org/10.18799/24131830/2026/8/5340